Mycorrhizal symbioses and the evolution of trophic modes in plants. (28th March 2019) - Jacquemyn, Hans; Merckx, Vincent S. F. T.
Abstract: Since the early colonization of land, plants depend, to various extents, on mycorrhizal fungi to meet their nutrient demands. In most mycorrhizal symbioses, plants provide sugars derived from photosynthesis to the fungi, whereas the fungi provide essential minerals to the plant. However, in some plants, the flow of carbon has reversed and the fungi provide carbon to the plants. These plants are called mycoheterotrophs. However, it remains unclear how and under which circumstances trophic modes change and whether transitions in trophic modes are associated with changes in mycorrhizal communities. Here, we review the available literature on mycorrhizal associations and trophic modes in plants. We first outline how trophic modes can be determined and how they differ across plants. We then investigate the evolutionary context under which mycoheterotrophy originated. We also examine the mycorrhizal communities associating with autotrophic, partially mycoheterotrophic and fully mycoheterotrophic plants within different plant families and investigate whether commonalities can be observed. Our overview shows that mycoheterotrophy has originated more than 40 times through evolutionary time and can be found in a wide range of plant groups, including liverworts, lycophytes, ferns, monocots and dicots. Partial mycoheterotrophy appears to be much more common than previously anticipated and represents an almost continuous gradient between autotrophy and full mycoheterotrophy. Comparison of the mycorrhizal communities associating with autotrophic, partial and full mycoheterotrophic plants indicates that, although they share some commonalities, shifts from autotrophy to full mycoheterotrophy are accompanied by either losses or shifts in mycorrhizal partners, suggesting that full or partial loss of photosynthesis selects for different mycorrhizal communities. Synthesis. Partial mycoheterotrophy appears to be much more common than previously thought and represents an almost continuous gradient from autotrophy to full mycoheterotrophy. Evolution to full mycoheterotrophy is challenging as it requires specific adaptations and often a switch to other mycorrhizal partners. More detailed analyses of the functionality of different mycorrhizal systems co‐occurring in the roots of a single plant and the costs of mycorrhizal switching are needed to understand the precise mechanisms leading to full mycoheterotrophy. Abstract : The mycorrhizal symbiosis represents a mutualism in which root‐associated fungi facilitate plants with the acquisition of essential nutrients from the soil, and in return, plants generally transfer photosynthetically fixed carbon to their fungal partners. Some plant lineages, however, evolved the ability to obtain carbon from fungi, a nutritional mode known as mycoheterotrophy. In this paper, we show that partial mycoheterotrophy, the ability to obtain carbon from fungi throughout the life cycle in combination with photosynthesis, is much more common than previously anticipated and represents an almost continuous gradient between autotrophy and full mycoheterotrophy.